Genetic diversity and genome-wide association analysis of pine wood nematode populations in different regions of China - Aixia, Yang; Xiaolei, Ding; Yuan, Feng; Ruiwen, Zhao; Jianren, Ye (Frontiers in Plant Science, 2023)
Pine wilt disease (Bursaphelenchus xylophilus) was recently detected in Liaoning Province, which was previously considered an unfavourable area for B. xylophilus due to its low temperatures. This study aims to compare the reproductivity and genetic variations of B. xylophilus isolates from Liaoning Province and other parts of China to explore their phenotypic and genomic differences. A reproductivity experiment showed that Liaoning isolates have higher reproductive ability at 15 ℃. Subsequent SNP profiling and population differentiation analysis revealed obvious genetic differentiation of Liaoning isolates from other isolates. A genome-wide association study showed that SNPs closely related to low-temperature tolerance were mainly located in GPCR, Acyl-CoA, and Cpn10, which are responsible for adaptation to environmental factors, such as temperature change. Pine wood nematodes likely adapted to the climate in Liaoning and maintained a certain reproductive capacity at low temperature via variants of adaptation-related genes. This study provides a theoretical basis for elucidating the prevalence and diffusion status of B. xylophilus in China.